2019
DOI: 10.1016/j.abd.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Chromoblastomycosis caused by Rhinocladiella aquaspersa: first case report in Guatemala

Abstract: The authors report a case of 40-year-old male patient with a five-year history of chromoblastomycosis on his right leg. Diagnosis was performed by direct 40% KOH exam of skin scales, culture with micro- and macromorphologic analysis, and genotypic characterization (sequencing of a fragment of the ITS region and phylogenetic analysis) of the isolated fungus. Rhinocladiella aquaspersa was identified as the etiological agent. Initially, the treatment was with oral itraconazole 200 mg/day for one year. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In fact, it was demonstrated that antifungal drugs need to be employed longer than 5 months to eliminate the etiologic agents of CBM. 13,14 On the other hand, patients treated with acitretin and imiquimod healed the lesions in the 5th month of therapy, suggesting that this association was effective at healing skin lesions (Figure 1g) in a short period of time in comparison with classical treatment. Although this association was effective, it is still important to note that first-line drugs, such as itraconazole and terbinafine -combined or not with imiquimodshould be employed as the standard treatment of CBM, especially in chronic and extensive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was demonstrated that antifungal drugs need to be employed longer than 5 months to eliminate the etiologic agents of CBM. 13,14 On the other hand, patients treated with acitretin and imiquimod healed the lesions in the 5th month of therapy, suggesting that this association was effective at healing skin lesions (Figure 1g) in a short period of time in comparison with classical treatment. Although this association was effective, it is still important to note that first-line drugs, such as itraconazole and terbinafine -combined or not with imiquimodshould be employed as the standard treatment of CBM, especially in chronic and extensive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Species of the genus Rhinocladiella have been described as less common agents of chromoblastomycosis 31,32 , i.e. R. aquaspersa, R. similis and R. tropicalis 3 .…”
Section: Discussionmentioning
confidence: 99%